Al-Zubair Pasha Rahma and his role in organizing the Bahr el-Ghazal District( 1831 – 1913 ) (Journal of the College of Basic Education, 2024)
The research dealt with studying the personality of Al-Zubayr Pasha Rahma and explaining his role in South Sudan in general and Bahr Al-Ghazal in particular, as this personality had a major role in the modern history of Sudan, especially the period of Ottoman-Egyptian rule in Sudan, where he worked to support and consolidate the influence of Egyptian rule in Darfur, in addition to his role in establishing a kingdom in Bahr al-Ghazal and its impact on spreading the Islamic religion and the Arabic language in Bahr al-Ghazal and Darfur and establishing a regular military army in Sudan. He also worked to develop the Bahr al-Ghazal District and eliminated individual differences between the people of northern and southern Sudan. Al-Zubair is considered the figure who laid important foundations for building contemporary Sudan.The research was divided into an introduction, three sections, and a conclusion in which his birth and upbringing were explained, and dealt with the beginning of his work in trade in southern Sudan and his role in organizing the Bahr al-Ghazal District, and a study of the detention of Al-Zir Pasha in Cairo, placing him under house arrest, then his return to Sudan until his death, and a conclusion with the most important results that I reached.